Proceedings Computer Graphics International CGI-99 1999
DOI: 10.1109/cgi.1999.777958
|View full text |Cite
|
Sign up to set email alerts
|

Volume decimation of irregular tetrahedral grids

Abstract: Rendering

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
(11 reference statements)
0
7
0
Order By: Relevance
“…Van Gelder et al [18] have already demonstrated that the mass-metric is superior to the density-metric. The massmetric is based on the changes in mass (the integral of density over a volume) of the material during decimation.…”
Section: Gradient Magnitude Based Error Metricsmentioning
confidence: 99%
See 2 more Smart Citations
“…Van Gelder et al [18] have already demonstrated that the mass-metric is superior to the density-metric. The massmetric is based on the changes in mass (the integral of density over a volume) of the material during decimation.…”
Section: Gradient Magnitude Based Error Metricsmentioning
confidence: 99%
“…Chopra and Meyer [2] have introduced an algorithm to take all of the four vertices of a tetrahedron, and fuse them onto the barycenter of the tetrahedron, while still taking care of complex mesh-inconsistency problems. Van Gelder et al [18] have presented a method for rapidly decimating volumetric data defined on a tetrahedral grid. They compared the mass-based and density-based decimation error metrics, and the mass-based metric is found to be superior.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Van Gelder et al [5] remove vertices based on mass and data error metrics. Uesu et al [6] provide a fast point-based method which works directly on the underlying scalar field.…”
Section: Related Workmentioning
confidence: 99%
“…Preventing inversion by explicit orientation checks is quite common. It has been used for planar graphs [Ciarlet and Lamour 1996], triangular meshes Hoppe 1996;Ronfard and Rossignac 1996], and tetrahedral volumes [Staadt and Gross 1998;Gelder et al 1999;Trotts et al 1999;Cignoni et al 2000;Chopra and Meyer 2002]. In our quadric-based system, it is in planar regions where mesh inversions are most likely to occur.…”
Section: Preventing Mesh Inversionmentioning
confidence: 99%